How do international remittances respond to real exchange rate movements? - Michael F. Bleaney; Mo Tian (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2019)
Shifts in the bilateral real exchange rate between the countries of migrants' origin and destination alter the real value of international remittances in origin currency relative to their real value in destination currency. Theoretical models predict a response in the form of some adjustment in remittances, measured in either currency. We construct real effective exchange rates weighted by migrant stocks for a large sample of countries to investigate the matter empirically. The evidence shows that remittances as a share of destination countries' GDP tend to remain virtually unchanged, so that real exchange rate movements predominantly affect the real value of remittances in terms of origin countries' currency. Possible explanations of this are discussed.
Keywords: F31; 330; exchange rates; migration; remittances